Tantangan dan Peluang dalam Penyebaran Islam pada Kemajuan Teknologi: Challenges and Opportunities in the Spread of Islam in Technological Advances - Dwezille Satritama Ghazali; Maurisa Asry Ramadhani; Muh. Danar Prakoso; Muh. Hafizh Nafi’ Maftazany; Muh. Ilham Perdana; Rakha Hadimulya; Sefira Dona Puspita (Litera Academica Publishing, 2024)
The development of information and communication technology has had a significant impact on the spread of Islam in the era of globalization. Technology not only speeds up the process of conveying information, but also allows Muslims to access religious teachings in a more efficient and effective way. This research aims to analyze the relationship between Islam and technological progress, as well as identifying the challenges and opportunities faced in the process of spreading Islamic teachings through technology. This research uses a literature review method by analyzing various scientific works related to the spread of Islam and technological developments. The results of this research reveal that technology offers great opportunities in Islamic da'wah, such as facilitating access to Islamic information through Islamic applications, expanding the reach of da'wah through social media, and enabling the spread of Islam to non-Muslims in a more peaceful and educative way. However, on the other hand, technology also brings challenges, such as the spread of misinformation, content that is not in accordance with Islamic values, as well as the potential for conflict and disruption to the focus of worship. Therefore, it is important for Muslims to use technology wisely and based on Islamic values ​​so that the spread of Islamic teachings can run effectively and harmoniously in facing the challenges of the times.